Occlusal contacts evaluation along orthodontic treatment with clear aligners and fixed appliance (Research, Society and Development, 2021)
The present research aim was to assess how occlusal contacts change along the initial 6 months of orthodontic treatment with fixed appliance and clear aligners. A sample with 40 patients was divided into 2 groups: Clear Aligners (CA) and Fixed Appliance (FA). In order to register occlusal contacts, patients were posit and instructed about how bite in habitual maximum intercuspidation. Registrations were perfomed monthly along 6 starting treatment months and noted in an occlusogram. A parametric test was applied to evaluate data since it presented a normal distribution according to Shapiro-Wilk test. For inter- and intergroup data analysis the Anova test was performed with a 5% significance level. Statistical tests were executed on Jamovi software (Jamovi Stats, Version1.2, Sydeney, Australia). There was a reduction in the amount of occlusal contacts for indivduals from both groups, CA and FA. Such reduction was more significative in the 3 starting months for FA group and between 3rd and 4th months for CA group. Therefore, the sort orthodontic appliance had no significant influence over occlusal contacts.